2011
DOI: 10.1080/1523908x.2011.560449
|View full text |Cite
|
Sign up to set email alerts
|

Rhetoric and Reporting of Public Participation in Landscape Policy

Abstract: Conrad, E., Cassar, L. F., Jones, M., Eiter, S., Izaovicova, Z., Barankova, Z., Christie, M., Fazey, I. (2011). Rhetoric and Reporting of Public Participation in Landscape Policy. Journal of Environmental Policy & Planning, 13 (1), 23-47, Article Number: PII 935334210.The involvement of the public in decision-making is established as a key feature of many planning policies. However, there is evidence from the literature of a prevailing gap between participation rhetoric on paper and participation at the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 57 publications
0
58
0
2
Order By: Relevance
“…A similar situation exists in landscape planning practice where decisions are based on professional's outsider based values missing the intimacy and subjectivity of the insiders who directly experience the landscape (Butler and Berglund, 2014;Conrad, Cassar, Jones, Eiter, Izaovičová, Barankova, Christie and Fazey, 2011). This is made evident in the increasingly sophisticated approaches landscape modelling which remain disconnected from social realities (Ryan, 2011).…”
Section: "An Area As Perceived By People Whose Character Is the Resmentioning
confidence: 99%
“…A similar situation exists in landscape planning practice where decisions are based on professional's outsider based values missing the intimacy and subjectivity of the insiders who directly experience the landscape (Butler and Berglund, 2014;Conrad, Cassar, Jones, Eiter, Izaovičová, Barankova, Christie and Fazey, 2011). This is made evident in the increasingly sophisticated approaches landscape modelling which remain disconnected from social realities (Ryan, 2011).…”
Section: "An Area As Perceived By People Whose Character Is the Resmentioning
confidence: 99%
“…A review of how the EU legislation translates into policies led by the EU member states has been made. From this analysis, we learn what kind of legislative support the public has for being involved in spatial planning, and how the EU legislation impacts the public participation policies led in the EU member states, as described by Baloh et al (2014), Conrad et al (2011) andVerovšek (2012). ■ The second area of research is stakeholder inclination towards participation.…”
Section: Materials and Methods Of Workmentioning
confidence: 99%
“…All directly or indirectly call for the active participation of citizens in procedures of spatial planning and simultaneously warn about the necessity of improving the dialog between authorities, inhabitants and the economic sector. »There is, however, evidence from the literature of a gap between participation rhetoric in policies and participation as practice at the operational level« (Conrad et al, 2011).…”
Section: Legislative Basis For Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…These expert-based approaches to landscape assessment-also called indirect methods-have been called into question, however, as both their production and application tend to be dominated by professionals rather than the communities in the target landscapes [89,116], and their role in policy tends to follow the "deficit model", which posits policy-makers as neutral guardians of the public trust who simply need to be provided with reliable scientific information in order to make decisions that contribute to sustainability [117]. In a review of 52 LCAs undertaken in the UK between 2007 and 2011, for instance, Butler and Berglund (2014) [118] found that many of them limited public input to responses to expert views of the landscape, with only one quarter of the assessments involving significant public engagement according to the authors' criteria.…”
Section: Landscape Character Assessment and Landscape Studies Based Omentioning
confidence: 99%